Pengaruh Pelatihan dan Kompetensi terhadap Kinerja Karyawan: Peran Mediasi Motivasi Kerja pada Pengguna SAP Plant Maintenance - Muhammad Ikhsan; Afriyadi Cahyadi; Yomeini Margareth (Universitas Muhammadiyah Pontianak, 2026)
Employee performance in ERP-based organizations depends on employees' competencies and motivation. This study examines the effects of training and competence on employee performance through work motivation among SAP Plant Maintenance users at PT Pupuk Sriwidjaja Palembang. Using a quantitative explanatory design, data from 372 respondents were analyzed with Partial Least Squares Structural Equation Modeling (PLS-SEM). The results show that competence and work motivation significantly improve employee performance, whereas training affects performance indirectly through work motivation. These findings imply that organizations should strengthen competency development and foster work motivation to maximize the effectiveness of training and improve workforce performance.